A Systematic Review of Innovative Software Project Management - Maranhão, Robson; Marinho, Marcelo; de Moura, Hermano (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2015)
Nowadays, innovation is one of the keys to success in organization and project management has become an important way to improve it. Innovative Software Projects (ISP) have a high level of uncertainty andcomplexity, so we need a specific approach to manage those threats. This paper presents a systematic literature review of Innovative Software Project Management (ISPM), helping to identify the factors that affect ISP and their management such as tools, techniques, processes, practices, organizational capabilities and IT assets; and how managers can prepare themselves for the challenges of their innovative projects. This paper aims to contribute to the improvement and success of project management in organizations.